Study on a dense theta pinch plasma for ion beam stripping application for FAIR - Cistakov, K.; Christ, P.; Manganelli, L.; Gavrilin, R.; Khurchiev, A.; Savin, S.; Iberler, M.; Jacoby, J. (Recent Contributions to Physics, 2020)
The transfer of ions to a higher charge state is of central importance for the development of new accelerator facilities. That is why the comparative analysis of the current stripping alternatives is a relevant topic. Currently, mainly gas and foil strippers are used for increasing the particle charge state. Even when their efficiency or lifetime has proved to be less than optimal, as these alternatives either require great effort or are not suitable. Compared to the gas and foil stripper the alternative of using a plasma stripper has a much higher effectiveness and a higher lifetime [1-13] That is why the plasma stripper has been proposed for the FAIR project (Facility for Antiproton and Ion Research) in Darmstadt, Germany.To further develop this subject, the plasma physics group of the Institute of Applied Physics at the University of Frankfurt is researching on an alternative for the Z-pinch plasma cell. During our research, various prototypes and solutions have been investigated [4-6], [8], [11], [14-16]. As a result, the optimal ignition criterion for the inductively coupled plasma ignition was determined, the optimal geometry of the discharge vessel, the required particle density and temperature of the plasma were calculated. Different coil configurations have been developed, built and tested. With some of them (spherical theta pinch and spherical screw pinch), beam time experiments were performed.This contribution presents the current state of plasma strippers with fully ionized hydrogen with simultaneously high particle densities in the range of some 1016 cm-3 for FAIR. Charge distributions after the ion beam plasma and ion beam cold gas interactions were measured and compared. As expected, the effective state of charge after interaction with plasma was higher than after interaction with gas (qp = 32.84 versus qgas = 29.41).
Keywords: plasma physics; ion stopping; ion stripping; accelerator physics; energy loss; charge distribution